Otimização de pilares retangulares em concreto armado submetidos à flexocompressão reta - Bordignon, Rodrigo (2010)
Search for a project that meets the performance and safety with minimal cost and, more than ever, minimal environmental impact was always the goal desired by design engineers. In general, the design of conventional reinforced concrete is an iterative process and it is based on the practice rules reasoned on experience and intuition of the designer, which makes this exhaustive process and only occasionally can lead to the best structural solution. This work presents the development and implementation of a mathematical formulation for obtaining optimal cross section of reinforced concrete columns subjected to uniaxial bending, based on the verification of the strength, according to the recommendations of the Brazilian standard ABNT NBR 6118 (2007). The design variables, considered as discrete, were the dimensions of the concrete section and the number and diameters of the steel bars, aiming to minimize the cost of cross section. The optimization was performed using the Simulated Annealing method. Some examples were produced by comparing the results to those obtained based on the conventional design procedure and with other optimization methods, also aiming to identify the influence of resistance class, variation in efforts and material costs in the optimal design of the sections